Rancang Bangun Sistem Informasi Penjualan Pada PT Hastika Telekomunikasi Kencana - Ega Shela Marsiani (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
This Sales Information System Design is created with the aim of easing agency’s buying and selling transactions in large quantities often called wholesalers until the proof of transaction in the form of receipts are printed. The methods used in this research are an interview approach and a literature study in the related agency, namely PT. Hastika Telekomunikasi Kencana Tebet Jakarta. The result of this research is an application that can help PT. HastikaTelekomunikasi Kencana in making the proof of payment and of various buying and selling transactions and in providing more guaranteed data security